2018
DOI: 10.3389/fbioe.2017.00083
|View full text |Cite
|
Sign up to set email alerts
|

An Online Respiratory Quotient-Feedback Strategy of Feeding Yeast Extract for Efficient Arachidonic Acid Production by Mortierella alpina

Abstract: Mortierella alpina (M. alpina) is well known for arachidonic acid (ARA) production. However, low efficiency and unstableness are long existed problems for industrial production of ARA by M. alpina due to the lack of online regulations. The aim of the present work is to develop an online-regulation strategy for efficient and stable ARA production in industry. The strategy was developed in 50 L fermenters and then applied in a 200 m3 fermenter. Results indicated that yeast extract (YE) highly increased cell grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 44 publications
1
11
0
Order By: Relevance
“…Time courses of glucose consumption rate, lycopene production, and cell OD 600 in BR + 3 g/L YE groups are similar to the YE group (Supplementary Material), which means that addition of 3 g/L yeast extract in the biomass residue group could sufficiently provide microelement, vitamins, and nucleotides which may not exist in biomass residue. Yeast extract is identified as significant factor for producing many valuable nutrition like arachidonic acid, docosahexaenoic acid, astaxanthin, and beta-carotene (Kusdiyantini et al, 1998;Bhosale and Gadre, 2001;Quilodrán et al, 2010;Li et al, 2018). The same phenomenon is also observed in this study.…”
Section: Effect Of Wastewater and Biomass Residue Replacement On Lycosupporting
confidence: 81%
See 1 more Smart Citation
“…Time courses of glucose consumption rate, lycopene production, and cell OD 600 in BR + 3 g/L YE groups are similar to the YE group (Supplementary Material), which means that addition of 3 g/L yeast extract in the biomass residue group could sufficiently provide microelement, vitamins, and nucleotides which may not exist in biomass residue. Yeast extract is identified as significant factor for producing many valuable nutrition like arachidonic acid, docosahexaenoic acid, astaxanthin, and beta-carotene (Kusdiyantini et al, 1998;Bhosale and Gadre, 2001;Quilodrán et al, 2010;Li et al, 2018). The same phenomenon is also observed in this study.…”
Section: Effect Of Wastewater and Biomass Residue Replacement On Lycosupporting
confidence: 81%
“…In addition, the contents of amino acid are different in biomass residue and yeast extract. Yeast extract is a widely used multi-functional nitrogen source in microbial fermentation industry (Li et al, 2018). Though the content of nitrogen and phosphorus in biomass residue are lower than in yeast extract, the species of amino acid shows no difference in both the two nitrogen sources.…”
Section: Composition Analysis Of Yeast Extract Biomass Residue and mentioning
confidence: 99%
“…Additionally, intracellular availability of oxygen plays a key role in CA biosynthesis, considering the oxidation steps catalyzed by the enzyme clavaminate synthase [48]. According to Li et al [49], the RQ values close to 1 observed in both reactors during the first hours of cultivation (see Figure 3b), indicate a balanced metabolism consistent with the aerobic oxidation of glycerol and glutamate as carbon sources present in the media. During the fed-batch operation the appearance of phosphate limitation led to a rapid decline in the RQ showing the increase of oxygen demand in this stage.…”
Section: Discussionmentioning
confidence: 58%
“…These results suggest the RQ as an additional parameter to consider in S. clavuligerus cultivations for CA production in connection with the macromorphology and the hydrodynamic conditions. In this regard, an online RQ-control approach could be applied to S. clavuligerus as a strategy to promote changes in carbon fluxes and therefore, the synthesis of the desired products [49,53].…”
Section: Discussionmentioning
confidence: 99%
“…When using molasses as substrate, keeping the RQ to a value of 1 during the cultivation aims to maintain metabolism in a state optimised for biomass formation [30]. During the propagation process, the RQ can be calculated and recorded online, based on oxygen and CO 2 content in the outlet gas, measured by gas analysis [31].…”
Section: Introductionmentioning
confidence: 99%